New Trigger for Stroke-like Episode in Sturge–Weber Syndrome: A Case Report - Emiliano Altavilla; Andrea De Giacomo; Anna Maria Greco; Fernanda Tramacere; Marilena Quarta; Daniela Puscio; Massimo Corsalini; Sara Pistilli; Dario Sardella; Flavia Indrio (Children)
Background. Sturge–Weber syndrome (SWS) is a rare non-hereditary neurovascular disorder characterized by capillary–venous malformations on the face, ocular vascular anomalies, and leptomeningeal capillary–venous malformations. Patients with SWS often experience cerebral perfusion impairment, increasing their risk for stroke-like episodes, seizures, and motor and cognitive impairments. Methods. We report the case of a 2-year-old boy diagnosed with SWS who developed a stroke-like episode following dye laser therapy under deep sedation. Results. Despite initial diagnostic challenges and persistent seizures, appropriate management led to full neurological recovery. Conclusions. This case highlights the importance of considering stroke-like episodes in children with SWS after stressful events such as medical procedures.